The Compton neutron Hafnium detector: electric charge generation rate - Azhazha, R.; Bogdan, E.; Gann, V.; Kovtun, K.; Kutny, V.; Pudov, O.; Rybka, А.; Soldatov, S.; Ulybkin, A. (Вопросы атомной науки и техники, 2022)
The properties of a Compton neutron detector with the emitter of metallic Hf were studying in this work. Using the previously calculated the emitter material nuclide composition during reactor irradiation, the dependence of the emitter signal value on the irradiation time was obtained with a step of 1 year for 5 years. It is shown that the composition modification due to nuclear transmutations changes the rate of an electric charge generation in the emitter. Досліджувалися властивості комптонівського нейтронного детектора з емітером із металічного Hf. Використовуючи розрахований раніше нуклідний склад матеріалу емітера в умовах реакторного опромінення, отримано залежність значення сигналу емітера від часу опромінення з кроком 1 рік протягом 5 років. Показано, що модифікація складу внаслідок ядерних трансмутацій змінює швидкість генерації електричного заряду в емітері. Изучались свойства комптоновского детектора нейтронов с эмиттером из металлического Hf. Используя ранее рассчитанный нуклидный состав материала эмиттера при облучении реактора, была получена зависимость величины сигнала эмиттера от времени облучения с шагом 1 год в течение 5 лет. Показано, что модификация состава за счет ядерных трансмутаций изменяет скорость генерации электрического заряда в эмиттере.